BeatWalk: Personalized Music-Based Gait Rehabilitation in Parkinson’s Disease - Cochen De Cock, Valérie; Dotov, Dobromir; Damm, Loic; Lacombe, Sandy; Ihalainen, Petra; Picot, Marie Christine; Galtier, Florence; Lebrun, Cindy; Giordano, Aurélie; Driss, Valérie; Geny, Christian; Garzo, Ainara; et al. (Frontiers in Psychology, 2021)
Walking regularly in Parkinson’s disease has beneficial effects on movement and quality of life. Yet, patients usually show reduced physical activity compared to healthy older adults. Using auditory stimulation, such as music, can facilitate walking but patients vary significantly in their response to the stimulus. An individualized approach adapting musical tempo to patients’ gait cadence, and capitalizing on these individual differences, is likely to provide a rewarding experience, increasing motivation for walk in Parkinson’s disease. We aim to evaluate the observance, safety, tolerance, usability and enjoyment of a new smartphone application coupled with wearable sensors (BeatPark) delivering individualized musical stimulation for gate auto-rehabilitation at home. Forty-five patients with Parkinson’s disease underwent a one month, outdoor, gait rehabilitation program, using the BeatPark application (30 min/day, 5 days/week). The music tempo was aligned in real time to patients’ gait cadence while fostering an increase of +20% of the patient’s spontaneous cadence. Open label evaluation was based on BeatPark use measures, questionnaires and a six-minute walk test. Patients used the application 78.8 % (±28.2) of the prescribed duration and mostly enjoyed it, across the whole program. The application was considered as “easy to use” by 75% of the patients. Pain, fatigue and falls were not increased by BeatPark use. While using BeatPark, patients reduced their fear of falling, and improved their quality of life. After the program, they improved their gait parameters in the six-minute walk test without musical stimulation. BeatPark is an easy to use, safe and enjoyable musical application for individualized gait rehabilitation in Parkinson’s disease increasing ‘walk for exercise’ duration thanks to a high observance.